Sources et modèles des historiens anciens, 2 - Devillers, Olivier; Sebastiani, Breno Battistin (Scripta Antiqua, 2021)
Fruit of a large international collaboration, the present volume collects 35 papers produced by experts. Its chief aim is to provide a contribution to the studies on the writing of history in Greco-Roman Antiquity from Herodotus to the Byzantine Empire. All these inquiries give rise to re-readings of each historian's historiographical project: if there is one idea pervading all the texts here collected - the diversity of approaches was thought from the start to be the one of the hallmarks of the volume - it is that each testimony should be addressed by reallocating it in the context of its own production, since these testimonies shed light both upon the moment when they were written and the one they describe.